Surgical Site Infection Prevention Strategies in Cardiac Surgery: A Systematic Review - Hadi Sulistyo, Angger Anugerah; Ferawati, Ferawati; Ardianti, Ikha; Kurniati, Mei Fitria (Knowledge Dynamics, 2024)
Background: Cardiac surgery becomes one of surgical procedure that has potential for develop several complications including surgical site infection (SSI). Despite the case is still very common, SSI can be regarded as the most preventable, especially when the treatment approach used, because there are many risk factors associated with the target. This systematic review aims to assess the effectiveness of interventions strategies used to reduce the incident of SSI in cardiac surgery. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines provide a standardized framework for conducting and reporting systematic reviews. A comprehensive search was conducted across major electronic databases, The following database were PubMed, Scopus and ProQuest. The inclusion criteria were clinical and a randomized control trial published between 2018 to 2023. The primary outcome measure was SSI rates. Results: The studies encompassed diverse perioperative intervention strategies, such as pre operative nasal ointment, pre operative showering and shaving, chlorhexidine mouthwash, and negative pressure therapy. In total, 436.762 articles regarding SSI prevention strategies in cardiac surgery were found in this study. However, around 7 articles that were met with the criteria of this study. Conclusion: Actions to reduce the incidence of SSI are carried out at all perioperative stages. The action taken was modifying the intervention and also using additional therapy carried out by health workers.